You are on page 1of 5

1

Assignment 2 — Solutions 1/23/04 (revised 2/2/2004)

Problem 1.17

(a) From equation 1.54:

÷” 2
W = ÅÅÅÅÅÅÅÅ ‡ °“ F• 3 x
e0
2

In the language of equation 1.62, we're given Vi = 0 for i ∫ 1, V1 = 1, C11 ª C . So

÷” 2 ÷” 2
W = ÅÅÅÅÅ ‚ ‚ Ci j Vi V j = ÅÅÅÅÅ C11 = ÅÅÅÅÅ C = ÅÅÅÅÅÅÅÅ ‡ °“ F• 3 x ï C = e0 ‡ °“ F• 3 x
1 n n 1 1 e0
2 i=1 j=1 2 2 2

(b) Let F be the true potential. We can write Y = F + dY , where dY is arbitrary except that Y must satisfy the same
boundary conditions as F. This implies that dY must vanish on the boundaries, which we will use below:

÷” 2
C@YD ª e0 ‡ °“ Y• 3 x

÷” ÷” ÷” ÷”
V

C@YD - C@FD = e0 ‡ “ HF + dYL ÿ “ HF + dYL 3 x - e0 ‡ “ F ÿ “ F 3 x

÷” ÷” ÷” ÷”
V V

= e0 ‡ A2 “ F ÿ “ HdYL + “ HdYL ÿ “ HdYLE 3 x


V

From Green's first identity:

÷” ÷”
‡ AdY “ F + “ HdYL ÿ “ FE  x = ® dY ÅÅÅÅÅÅÅÅÅÅ a = 0 since dY§S = 0
2 3 ∑F
V S ∑n

The true potential must satisfy “2 F = 0 within V , so

÷” ÷”
C@YD - C@FD = -2 e0 ‡ dY “2 F 3 x + e0 ‡ °“ HdYL• 3 x = e0 ‡ °“ HdYL• 3 x ¥ 0
2 2
V V V

Hence we have shown that C@YD ¥ C@FD, where C@FD is the true capacitance.

Problem 1.22

(a)
Expand the second term in partial fractions:

1+
6

ij è!!!!!! è!!!!!! è!!!!!!


41 + 3 73 yz ij -41 + 3 73 yz
a = ÅÅÅÅÅ : 32 jjj¶ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz jjj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz > 0 ï ¶ > ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º -0.12
1 -41 + 3 73
2 k 128 {k 128 { 128

h = 1 + ¶ º 1 - 0.12 = 0.88 for a = 1 ê 2 in the quintic gives -0.031, which is close enough for government work (yes,
We can try applying this to a = 2, but the square root produces an imaginary number which is bad. Plugging in

it is negative, but if you let h be slightly more than 0.88 you will get a positive answer, which goes to show that we've
got it almost right).

Finally, we could repeat the whole process with h p 1, dropping positive powers of h smaller than h5 . But we know

case, which is around 0.62. Now we've tried h ` 1 and that didn't work, so the logical next guess would be h º 1 ê 2.
that this cannot give us the right answer because as we've argued we should find for a = 2 a value less than the a = 1

So let h = 1 ê 2 + ¶ for †¶§ ` 1, and repeat (this time I'll plug in a = 2 straight off since that's what we want):

19 157 ¶ 95 ¶2
ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ > 0

95 i è!!!!!!!!
! !!!! y i è!!!!!!!! ! !!!! y
ÅÅÅÅÅÅÅÅÅ jj¶ + ÅÅÅÅÅÅÅÅÅÅÅÅ I157 + 10209 Mzz jj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅ I-157 + 10209 Mzz > 0
16 8 2

2 k {k {
1 1

è!!!!!!!!!!!!!
760 760
¶ > ÅÅÅÅÅÅÅÅÅÅÅÅ I-157 + 10209 M º -0.074
1
760

Plugging h = 1 ê 2 + ¶ º 1 ê 2 - 0.074 º 0.426 into the quintic gives -0.021, which is again very good agreement with
the provided answer of h º 0.428.

This is of course all just a fancy way of making educated guesses as to how to utilize Newton's method with a reason-
ably small number of iterations, punchable into your trusty hand calculator.

Problem 2.7

(a) The easiest way is to use the method of images. The Green's function is simply the potential of a point charge

Dirichlet problem), so we imagine a charge at (in cylindrical coordinates) x” £ = Hv£ , f£ , z£ L and place an image charge
of 4 p e0 in empty space (here the z ¥ 0 volume) that satisfies the specified boundary conditions (here G§z=0 = 0 for a

at x” ≥ = Hv≥ , f≥ , z≥ L. The system is invariant under rotation about the z£ -axis, so we expect the image charge to be on
the z£ -axis as well (of course we're only allowed to put it below the plane). In fact the image should be exactly the

the z = 0 plane only if the placement of charges is symmetric about said plane. So we guess x” ≥ = Hv£ , f£ , -z£ L:
reflection of the point charge about the x -y plane with opposite charge — the lines of force will be perpendicular to

÷”, ÷x”£ L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ


÷†x” - ÷x”ÅÅÅÅ£ ŧŠ- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷†x” - ÷x”ÅÅÅÅ≥ÅÅÅŧ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷
÷ ” ÷÷÷”
†v - v + Hz - z L z§ ÷÷
÷ ” ÷÷÷”
†v - v + Hz + z£ L z` §
1 1 1 1
GHx £ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ`ÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
£

We see immediately that at z = 0 this gives zero as required.

÷” n-2
(b) We'll use ∑†b x” - c”§n ê ∑ x = n b °x” - b• Hb x - c” ÿ x` L which we computed in problem 2.2, with x” Ø z£ z` . In the
language of equation 1.44, r = 0 everywhere since there is no free charge distribution and F§z£ =0,v£ <a = V ,
F§z£ =0,v£ >a = 0. Remember that n£ is the outward pointing normal so n` £ = -z` and we will incur an overall minus sign.
7

÷”L = + ÅÅÅÅ1ÅÅÅÅÅÅ ÷”£ ∑G £


® FHx L ÅÅÅÅÅÅÅÅÅ£ÅÅÅ a = ÅÅÅÅÅÅÅÅÅÅ ‡ f£ ‡ v£ v£ ÅÅÅÅÅÅÅÅÅÅÅÅ
V 2p a ∑G
FHx

Hv ÷÷
÷ ” ÷÷
÷ ” £ L ÿ z` + z + z£
4p S ∑z 4p 0 ∑ z£
÷÷÷” - ÷÷v ÷”£ L ÿ z` + z - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
0

ÅÅÅÅÅÅÅÅÅÅÅÅ = -H-1L Hv ÷÷÷” - ÷÷v ÷”£ + Hz ÷÷÷” - ÷÷v ÷”£ + Hz


∑G £ - v
†v - z£ L z` §3 †v + z£ L z` §3
z ` ÿ z` = 0
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ ì v

∑ G ƒƒ
∑ z£

ÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ ÷÷
÷ ” ÷÷÷”£ + ”zÅÅÅŧÅ3ÅÅÅÅ
∑ z ƒz =0 †v - v
2z
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
£ £

÷”L = ÅÅÅÅ
ÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷÷” - ÷÷v ÷”£ + ”zÅÅÅŧÅ3ÅÅÅÅ
2p a v£
†v
Vz
FHx ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p 0 0

(c)

FHz”L = ÅÅÅÅÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷÷÷”£ + ”z§3 ‡ ‡


2p a v£ 2p a v£
†-v @Hv£ L2 + z2 D3ê2
Vz Vz £ £ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å ÅÅÅ = ÅÅÅÅ
Å ÅÅÅ
Å Å f v ÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÄÅ ÉÑa
2p 0 2p 0
ÅÅ ÑÑ i 1y i y
0 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ = V z jjjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ


= V z ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ è!!!!!!!!! ÅÅÅÅÅÅ + ÅÅÅÅÅ zzzz = V jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
!!!!!! è!!!!!!!! ! ÅÅÅÅÅÅ zzzz
!!!!!!
ÅÅÇ @Hv£ L2 + z2 D ÑÑÖ
-1 1 z
k z{ k a2 + z2 {
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
1ê2
0 a2 + z2

(d)

÷÷÷” - v
†v ÷÷÷”£ + ”z§2 = ÷÷÷” ÷÷÷”£ ” ÷÷÷” ÷÷÷”£ ” ÷÷÷” - v
÷÷÷”£ L ÿ Hv
÷÷÷” - v
÷÷÷”£ L + z2 = v2 - 2 v
÷÷÷” ÿ v
÷÷÷”£ + Hv£ L2 + z2
Hv - v + zL ÿ Hv - v + zL = Hv
i Hv£ L2 - 2 v ÷÷÷” ÿ v ÷÷÷”£ y
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz
= Iv2 + z2 M jjjj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
k v2 + z2 {

÷÷÷” ÿ v
Within the range of integration v£ § a, so @Hv£ L2 - 2 v ÷÷÷”£ D ê Hv2 + z2 L ` 1 and we may expand the above (and
powers thereof) using the binomial expansion

i n + k - 1 yz iny
H1 ≤ xL-n = ‚ jj z H¡ xLk , †x§ < 1 and n > 0 , jj zz ª ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

GHn + 1L
k { k m{
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
k=0
k GHm + 1L GHn - m + 1L

ij Hv£ L2 - 2 v ÷÷÷” ÿ v ÷÷÷”£ y-3ê2


÷”L = ÅÅÅÅ
ÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j ÅÅÅÅÅÅÅÅÅ zzzz
2p a v£
Hv2 + z2 L3ê2
Vz
k {
FHx ÅÅÅÅÅÅÅÅ
2p 0 0 v2 + z2

i -3 ê 2 + k - 1 zy ijj 2 v v cosHf - f L - Hv L yzz


f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ jj z jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz

= ÅÅÅÅÅÅÅÅÅÅ ‡
v£ £ £ £ 2
2p k

k {k
a

Hv2 + z2 L
Vz
{
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p 0 0 3ê2 k v +z 2 2
k=0

Note that Ÿ02 p f£ cosn Hf - f£ L to any odd n is zero because the integrand is odd. Also Ÿ02 p f£ cos2 Hf - f£ L = p. So

ÅÄÅ
÷”L = ÅÅÅÅ ÅÅ 3 2 v v£ cosHf - f£ L - Hv£ L2
ÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ1 + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p v£
Hv2 + z2 L ÅÅÇ
Vz a
FHx ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

ÉÑ
2p 0 0 3ê2 2 v2 + z2

15 ij 2 v v£ cosHf - f£ L - Hv£ L2 yz ÑÑ
Ñ
j
+ ÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz + …ÑÑÑÑ
z
2

8 k { ÑÑ
Ö
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
v2 + z2
i
j Hv L 4 v2 Hv£ L2 p + 2 p Hv£ L4 y
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzzz
= ÅÅÅÅÅÅÅÅÅÅ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj2 p - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a v £ p £ 2

Hv + z L Hv + z L
Vz 3 2 15
2p 0 k v {
3ê2 2 + z2 4

ij a2 y
2 8 2 2

a4 ê 4 15 4 v2 a4 ê 4 + 2 a6 ê 6
2 2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzzz
jj2 ÅÅÅÅÅÅÅÅÅ - 3 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j
2 Hv2 + z2 L3ê2 Hv2 + z2 L
Vz 1
k 2 {
= ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
v +z 2 2 4

i
8

j y
z
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzz
2 2 5 3 v a + a4 2 2

2 Hv2 + z2 L3ê2 k 8 Hv2 + z2 L4


Va z 3 a
4 v2 + z2 {
Expand the second term in partial fractions:

1+
6

ij è!!!!!! è!!!!!! è!!!!!!


41 + 3 73 yz ij -41 + 3 73 yz
a = ÅÅÅÅÅ : 32 jjj¶ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz jjj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz > 0 ï ¶ > ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º -0.12
1 -41 + 3 73
2 k 128 {k 128 { 128

h = 1 + ¶ º 1 - 0.12 = 0.88 for a = 1 ê 2 in the quintic gives -0.031, which is close enough for government work (yes,
We can try applying this to a = 2, but the square root produces an imaginary number which is bad. Plugging in

it is negative, but if you let h be slightly more than 0.88 you will get a positive answer, which goes to show that we've
got it almost right).

Finally, we could repeat the whole process with h p 1, dropping positive powers of h smaller than h5 . But we know

case, which is around 0.62. Now we've tried h ` 1 and that didn't work, so the logical next guess would be h º 1 ê 2.
that this cannot give us the right answer because as we've argued we should find for a = 2 a value less than the a = 1

So let h = 1 ê 2 + ¶ for †¶§ ` 1, and repeat (this time I'll plug in a = 2 straight off since that's what we want):

19 157 ¶ 95 ¶2
ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ > 0

95 i è!!!!!!!!
! !!!! y i è!!!!!!!! ! !!!! y
ÅÅÅÅÅÅÅÅÅ jj¶ + ÅÅÅÅÅÅÅÅÅÅÅÅ I157 + 10209 Mzz jj¶ - ÅÅÅÅÅÅÅÅÅÅÅÅ I-157 + 10209 Mzz > 0
16 8 2

2 k {k {
1 1

è!!!!!!!!!!!!!
760 760
¶ > ÅÅÅÅÅÅÅÅÅÅÅÅ I-157 + 10209 M º -0.074
1
760

Plugging h = 1 ê 2 + ¶ º 1 ê 2 - 0.074 º 0.426 into the quintic gives -0.021, which is again very good agreement with
the provided answer of h º 0.428.

This is of course all just a fancy way of making educated guesses as to how to utilize Newton's method with a reason-
ably small number of iterations, punchable into your trusty hand calculator.

Problem 2.7

(a) The easiest way is to use the method of images. The Green's function is simply the potential of a point charge

Dirichlet problem), so we imagine a charge at (in cylindrical coordinates) x” £ = Hv£ , f£ , z£ L and place an image charge
of 4 p e0 in empty space (here the z ¥ 0 volume) that satisfies the specified boundary conditions (here G§z=0 = 0 for a

at x” ≥ = Hv≥ , f≥ , z≥ L. The system is invariant under rotation about the z£ -axis, so we expect the image charge to be on
the z£ -axis as well (of course we're only allowed to put it below the plane). In fact the image should be exactly the

the z = 0 plane only if the placement of charges is symmetric about said plane. So we guess x” ≥ = Hv£ , f£ , -z£ L:
reflection of the point charge about the x -y plane with opposite charge — the lines of force will be perpendicular to

÷”, ÷x”£ L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ


÷†x” - ÷x”ÅÅÅÅ£ ŧŠ- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷†x” - ÷x”ÅÅÅÅ≥ÅÅÅŧ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷
÷ ” ÷÷÷”
†v - v + Hz - z L z§ ÷÷
÷ ” ÷÷÷”
†v - v + Hz + z£ L z` §
1 1 1 1
GHx £ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ`ÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
£

We see immediately that at z = 0 this gives zero as required.

÷” n-2
(b) We'll use ∑†b x” - c”§n ê ∑ x = n b °x” - b• Hb x - c” ÿ x` L which we computed in problem 2.2, with x” Ø z£ z` . In the
language of equation 1.44, r = 0 everywhere since there is no free charge distribution and F§z£ =0,v£ <a = V ,
F§z£ =0,v£ >a = 0. Remember that n£ is the outward pointing normal so n` £ = -z` and we will incur an overall minus sign.
7

÷”L = + ÅÅÅÅ1ÅÅÅÅÅÅ ÷”£ ∑G £


® FHx L ÅÅÅÅÅÅÅÅÅ£ÅÅÅ a = ÅÅÅÅÅÅÅÅÅÅ ‡ f£ ‡ v£ v£ ÅÅÅÅÅÅÅÅÅÅÅÅ
V 2p a ∑G
FHx

Hv ÷÷
÷ ” ÷÷
÷ ” £ L ÿ z` + z + z£
4p S ∑z 4p 0 ∑ z£
÷÷÷” - ÷÷v ÷”£ L ÿ z` + z - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
0

ÅÅÅÅÅÅÅÅÅÅÅÅ = -H-1L Hv ÷÷÷” - ÷÷v ÷”£ + Hz ÷÷÷” - ÷÷v ÷”£ + Hz


∑G £ - v
†v - z£ L z` §3 †v + z£ L z` §3
z ` ÿ z` = 0
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ ì v

∑ G ƒƒ
∑ z£

ÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ ÷÷
÷ ” ÷÷÷”£ + ”zÅÅÅŧÅ3ÅÅÅÅ
∑ z ƒz =0 †v - v
2z
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
£ £

÷”L = ÅÅÅÅ
ÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷÷÷” - ÷÷v ÷”£ + ”zÅÅÅŧÅ3ÅÅÅÅ
2p a v£
†v
Vz
FHx ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p 0 0

(c)

FHz”L = ÅÅÅÅÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷÷÷”£ + ”z§3 ‡ ‡


2p a v£ 2p a v£
†-v @Hv£ L2 + z2 D3ê2
Vz Vz £ £ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å ÅÅÅ = ÅÅÅÅ
Å ÅÅÅ
Å Å f v ÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÄÅ ÉÑa
2p 0 2p 0
ÅÅ ÑÑ i 1y i y
0 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ = V z jjjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ


= V z ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ è!!!!!!!!! ÅÅÅÅÅÅ + ÅÅÅÅÅ zzzz = V jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
!!!!!! è!!!!!!!! ! ÅÅÅÅÅÅ zzzz
!!!!!!
ÅÅÇ @Hv£ L2 + z2 D ÑÑÖ
-1 1 z
k z{ k a2 + z2 {
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
1ê2
0 a2 + z2

(d)

÷÷÷” - v
†v ÷÷÷”£ + ”z§2 = ÷÷÷” ÷÷÷”£ ” ÷÷÷” ÷÷÷”£ ” ÷÷÷” - v
÷÷÷”£ L ÿ Hv
÷÷÷” - v
÷÷÷”£ L + z2 = v2 - 2 v
÷÷÷” ÿ v
÷÷÷”£ + Hv£ L2 + z2
Hv - v + zL ÿ Hv - v + zL = Hv
i Hv£ L2 - 2 v ÷÷÷” ÿ v ÷÷÷”£ y
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz
= Iv2 + z2 M jjjj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
k v2 + z2 {

÷÷÷” ÿ v
Within the range of integration v£ § a, so @Hv£ L2 - 2 v ÷÷÷”£ D ê Hv2 + z2 L ` 1 and we may expand the above (and
powers thereof) using the binomial expansion

i n + k - 1 yz iny
H1 ≤ xL-n = ‚ jj z H¡ xLk , †x§ < 1 and n > 0 , jj zz ª ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

GHn + 1L
k { k m{
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
k=0
k GHm + 1L GHn - m + 1L

ij Hv£ L2 - 2 v ÷÷÷” ÿ v ÷÷÷”£ y-3ê2


÷”L = ÅÅÅÅ
ÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j ÅÅÅÅÅÅÅÅÅ zzzz
2p a v£
Hv2 + z2 L3ê2
Vz
k {
FHx ÅÅÅÅÅÅÅÅ
2p 0 0 v2 + z2

i -3 ê 2 + k - 1 zy ijj 2 v v cosHf - f L - Hv L yzz


f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ jj z jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz

= ÅÅÅÅÅÅÅÅÅÅ ‡
v£ £ £ £ 2
2p k

k {k
a

Hv2 + z2 L
Vz
{
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p 0 0 3ê2 k v +z 2 2
k=0

Note that Ÿ02 p f£ cosn Hf - f£ L to any odd n is zero because the integrand is odd. Also Ÿ02 p f£ cos2 Hf - f£ L = p. So

ÅÄÅ
÷”L = ÅÅÅÅ ÅÅ 3 2 v v£ cosHf - f£ L - Hv£ L2
ÅÅÅÅÅÅ ‡ f£ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ1 + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2p v£
Hv2 + z2 L ÅÅÇ
Vz a
FHx ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

ÉÑ
2p 0 0 3ê2 2 v2 + z2

15 ij 2 v v£ cosHf - f£ L - Hv£ L2 yz ÑÑ
Ñ
j
+ ÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz + …ÑÑÑÑ
z
2

8 k { ÑÑ
Ö
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
v2 + z2
i
j Hv L 4 v2 Hv£ L2 p + 2 p Hv£ L4 y
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzzz
= ÅÅÅÅÅÅÅÅÅÅ ‡ v£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj2 p - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a v £ p £ 2

Hv + z L Hv + z L
Vz 3 2 15
2p 0 k v {
3ê2 2 + z2 4

ij a2 y
2 8 2 2

a4 ê 4 15 4 v2 a4 ê 4 + 2 a6 ê 6
2 2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzzz
jj2 ÅÅÅÅÅÅÅÅÅ - 3 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j
2 Hv2 + z2 L3ê2 Hv2 + z2 L
Vz 1
k 2 {
= ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
v +z 2 2 4

i
8

j y
z
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + …zzz
2 2 5 3 v a + a4 2 2

2 Hv2 + z2 L3ê2 k 8 Hv2 + z2 L4


Va z 3 a
4 v2 + z2 {
8

Both results in (c) and (d) share the common range v = 0, z p a. Plugging this in to the last expression:

ij y ij y
FHz”L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + …zzz = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj1 - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + …zzz
j z j z
V a2 z 3 a2 5 a4 V a2 1 3 a2 5 a4
k { k {
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
2 z3 4 z 2 8 z 4 2 z2 4 z 2 8 z 4

Expanding the result in (c) in orders of a ê z gives the same thing (of course!):

ij yz ÄÅ É
jj zz Å i yÑÑ V a2 i y
FHz”L = V jjjj1 - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz = V ÅÅÅÅ1 - jj1 + ÅÅÅÅÅ J ÅÅÅÅÅ N + ÅÅÅÅÅ J ÅÅÅÅÅ N + ÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅ N + …zzÑÑÑÑ = ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ jjjj1 + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ + …zzzz
"#####################2# ÅÇ k {ÑÖ
1 1 a 2 3 a 4 5 a 6 3 a2 5 a4

k 1 + Ha ê zL { k {
2 z 8 z 16 z 2 z 2 4 z 2 8 z 4